The Use of Communicative Language Teaching (CLT) Method in Improving Students’ English Vocabulary - Asrul, Asrul; Dahlan, Suratman (JOLLT Journal of Languages and Language Teaching, 2022)
This study aims to determine whether the CLT method improves students’ English vocabulary mastery before and after learning using the CLT method. This is a quantitative study with a pre-experimental design. In this research design, the researcher only uses one class as an experimental class which was given treatment in the form of vocabulary learning using the CLT method. However, before the treatment was given, students would be given a test in the form of a pre-test and post-test that aimed to see the effect of the CLT method in improving students’ vocabulary skills. The data from the test was collected and then the data was analyzed through descriptive statistics. The population used was all students of SMP Negeri 50 Halmahera Selatan and all were selected as samples in this study. The instrument used to collect quantitative data in this study was a vocabulary test. This test is in the form of multiple choice consisting of 30 question items. Tests distributed before and after the treatment were given as pre-test and post-test. In addition to comparing the significance value (Sig.) with a probability of 0.05, the authors also compared the t-count value with the t-table to test the hypothesis that had been made previously. The t count based on the result of paired sample test is 38,076 and the t table based on the value of df (34) is 2,042. This shows that the value of t arithmetic (37.769) > t table (2.042) it can be concluded that H0 is rejected and Ha is accepted. In other words, there is an average difference between the learning outcomes of the pre-test and post-test, which means the CLT method improves the studentsâ€™ English vocabulary at SMP Negeri 50 Halmahera Selatan.